Prominent Muslim Leaders of Bengal in India’s Freedom Struggle (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
India has been a cradle of diverse cultures and a melting pot of ideas for millennia. This legacy of unity and inclusivity was carried forward by figures such as Emperor Ashoka, Emperor Akbar, the Bhakti and Sufi traditions, and later, thinkers like Rabindranath Tagore, KaziNazrul Islam, Mahatma Gandhi, Subhas Chandra Bose, and Dr. APJ Abdul Kalam.Historians note that between the Battle of Plassey (1757) and the Sepoy Rebellion (1857), the people of India participated in 54 uprisings against British rule. Prominent Muslim leaders played a crucial role in these movements. Additionally, they were actively involved in later struggles for independence, including the Khilafat Movement, Non-Cooperation Movement, Civil Disobedience Movement, Quit India Movement, and the Naval Mutiny of 1946.